Tenoxicam : uma possível alternativa terapêutica no tratamento das doenças vasculares cerebrais isquêmicas - Galvão, Rita Izabel Monteiro (2003)
The present work shows effects of tenoxicam (TXC ) in rats submitted to transient cerebral ischemia. Male aged Wistar rats (250-450g) were submitted to the both common carotid arteries occlusion with aneurysmal clips to induce ischemia. At the end of 45 min of bilateral carotid arteries occlusion (BCAO), blood flow was restored by releasing the clips and the incision was closed with a single suture. After 1h or 24h of reperfusion, the rats were decapitated, brains dissected and hippocampi removed for measurements of MPO activity, nitrite , monoamine , glutamate/aspartate, ATP, lactate and piruvate levels. The animals were divided in 5 groups (N=4-10): 1) sham-operated, 2) BCAO, 3) BCAO + TXC 2.5mg/kg, 4) BCAO + TXC10mg/kg and 5) sham-operated + TXC 10mg/kg . The TXC administration was made after 45 minutes of BCAO. The histological analysis were made and showed significant changes on group 2 in comparison with group 1 (p<0.05, Kruskal-Wallis and Dunn’ test). The use of TXC showed a tendency of decrease these alterations. The MPO activity in the group 2 was significantly greater than that in the group 1 (p< 0.0001, ANOVA and Tukey). The treatment with TXC reduced the MPO activity to control levels (p<0.0001, ANOVA and Tukey). There was increased levels of nitrite in the group 2 in comparison with group 1 (p<0.05), and the treatment with TXC failed to attenuate the ischemic levels. The hippocampal levels of DA were increased after ischemia when compared with group 1 (p<0.01, Anova e Dunnett ) and were reverted with TXC in both doses (p<0.01, Anova e Dunnett). Hippocampal level from group 2 of both glutamate and aspartate were higher than group 1 (p < 0.05 , ANOVA , Dunnett’s Test). Ischemia-induced elevations in glutamate and aspartate were not attenuated with TXC . The ATP levels have showed decreases in the group with 1 h of reperfusion in comparison with 24 h . The lactate levels were increased in the 24 h reperfusion’s group in relation of 1 h. These results indicated more metabolic damage in aged rats. So, the neuroprotective role of TXC is possibly through the anti-inflammatory action with inhibition of cyclooxygenase activity, and interfering on the inflammatory process of post-ischemic reperfusion. The TXC, therefore, could be a possible therapeutic alternative on stroke treatment like an adjunct drug associated with, for example, a thrombolitic.